Contribution of Leg Muscle Explotion Power, Arm Muscle Explotion Power and Waist Flexibility Against Smash Ability - arlidas - -; Aryadie Adnan (Performa, 2019)
The problem in this study is the lack of smash ability in volleyball athletes in Sangir Jujuan District, South Solok Regency. The purpose of this study was to determine the contribution of leg muscle explosive power, flexural muscle power and waist flexion to the smash ability of athletes in Sangir Jujuan District, South Solok Regency. This type of research is correlational.. The sampling technique uses total sampling. Thus the sample in this study amounted to 35 athletes. Instrumentation and data collection techniques are: 1) Leg muscle explosive power tested with a vertical jump, 2)) Arm muscle explosive power tested with two hand medicine ball put, 3) Determination of the waist in the test with trunk extension, 4) Ability to smash using a volleyball court who were given the appraisal plot. Data were analyzed with product moment correlation and multiple correlation with a significant level α = 0.05. The results of data analysis were obtained as follows: 1) Leg muscle explosive power contributed to the smash ability of 17.31%. 2) Arm muscle explosive power contributes to the smash ability of 21.60%. 3) Waist flexion contributes to the volleyball smash ability of Sangir Jujuan District, South Solok Regency by 13.94%. 4) Leg muscle explosive power, arm muscle explosive power and waist flexion jointly contributed to the smash ability of 52.85%.